Experimental Analysis of Seismic Performance of Masonry Shear Wall Reinforced with PP-Band Mesh and Plastering Mortar under In-Plane Cyclic Loading. (28th April 2020) - Zhou, Qiang; Yang, Lingyu; Zhao, Wenyang
Abstract : Masonry structures are widely used in developing countries due to their low cost and simple construction, especially in remote areas, where there are a large number of houses without seismic measures. These buildings are prone to collapse and cause a lot of casualties, even under the action of small earthquakes. For the reinforcement of this structure, a cheap, effective, and easy-to-construct reinforcement method is urgently needed. Therefore, this article studies the reinforcement method of polypropylene bands (PP-bands). We have carried out low-frequency cyclic loading tests for two PP-band reinforced masonry walls and two compared masonry walls. We mainly studied the influence of PP-band and different compressive strengths of plastering mortar on the masonry wall's seismic capacity. The seismic indicators mainly studied in this article include ultimate bearing capacity, energy dissipation capacity, stiffness degradation, and hysteresis characteristics. The experimental results show that the PP-band can greatly enhance the seismic capacity of the masonry wall. The ultimate bearing capacity, energy dissipation capacity, and displacement ductility of the PP-band reinforced wall are increased by 38%–48%, 22%–47%, and 138%–226%.